Identification of Rice Varieties of Assam Based on Grain Characters and Reaction to Certain Chemical Tests - RIMPI BORA; SHARMILA DUTTA DEKA; PRIYABRATA SEN (Seed Research, 2026)
Eleven local and popular rice varieties of Assam, were characterized on the basis of hulled and unhulled grain characters. Varieties were identified based on grain characters like grain colour, grain length, grain width, decorticated grain length, decorticated grain width, decorticated grain colour, decorticated grain shape, grain L/B ratio, grain type and 1000 grain weight. Rapid laboratory tests such as phenol, modified phenol, NaOH, FeSO4, KOH-resistance and peroxidase tests have also been used to identify and group the rice varieties.